A systematic review of tropical disease prevalence among migrants - Mohd Afiq Arifin; Chua Su Peng; Ummi Mirza Baharudin; Mohd Hafiz Baharudin; Muhammad Aklil Abd Rahim; Syed Sharizman Syed Abdul Rahim; Azman Atil; Mohd Faizal Madrim; Zulkhairul Naim Bin Sidek Ahmad; Khalid Mokti; Abdul Rahman Ramdzan; Mohammad Saffree Jeffree; et al. (Scientific Foundation SPIROSKI, Skopje, Republic of Macedonia, 2022)
BACKGROUND: Few studies have assessed the burden of tropical diseases among migrants into non-endemic countries. AIM: This study aimed to systematically review the existing data of the prevalence of tropical diseases globally, including neglected tropical diseases globally. MATERIALS AND METHODS: The authors conducted a systematic review reporting prevalence (including seroprevalence) of tropical diseases following the PRISMA guidelines and based on the database from PUBMED, WoS, and PROQUEST. All the identified records were screened according to the inclusion and exclusion criteria. The selected articles’ quality was appraised using the mixed methods appraisal tool to ensure its quality. RESULTS: Overall, 19 studies conducted in 13 countries published between the year 2017–2020 were included in the study. Based on the thematic analysis, two themes (type of organism) and 11 sub-themes (disease) were used. The prevalence of tropical diseases among migrants ranged from 0.2 to 31% for malaria; 3–20% for Chagas Disease; 3.2–3.5% for Giardiasis; 31.7–57.4% for Toxoplasmosis; 0.1–51%, for Schistosomiasis; 0.1–15.8%, for Strongyloidiasis; 0.3–3.8% for Trichuriasis; 0.2–0.9% for Ascariasis; 6.4–9.7% for Toxocariasis; 0.3% for Loiasis; and 0.5% for Filariasis. All migrants warrant thorough screening and testing, based on the country of origin of their last visit. Routine screening and follow-up may reduce the re-emergence of tropical disease in non-endemic countries. CONCLUSION: Multiple approaches in managing social and health issues among migrants are vital to secure healthy labor forces for the country’s economy and development. Public health sectors should implement strategic promotive, preventive, and curative programs targeted to this group